2015
DOI: 10.1080/13691058.2015.1005138
|View full text |Cite
|
Sign up to set email alerts
|

Women’s opinions on the legalisation of abortion in Chile 2009–2013

Abstract: Chile is one of only four countries in the world where there is no explicit legal exception to prohibitions on abortion, and where the criminalisation of abortion endangers women's health and may be misaligned with public opinion. In this study we explored attitudes towards the legalisation of abortion and differences in levels of support across time. Among Chilean women in 2009 and 2013, we examined: (1) an additive index indicating support for legalisation of abortion in several situations and (2) support fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
3
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 36 publications
(46 reference statements)
2
3
0
2
Order By: Relevance
“…The results of this study show that women who decide to undergo a VTP are the object of stigmatization by the participants with higher levels of religiosity. This is in line with the conclusions reached in other studies with Chilean (Palermo et al, 2015;Pérez et al, 2020) and Latin American populations (Marván et al, 2018;McMurtrie et al, 2012;Sorhaindo et al, 2016) and in more distant cultures (Cockrill et al, 2013;Shellenberg et al, 2014). Likewise, considering the dimensions of religiosity included in this study, we can state that in addition to the acceptance of normative codes stemming from religious dogmas, interaction with other religious people -family members or peers -plays a role in this influence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The results of this study show that women who decide to undergo a VTP are the object of stigmatization by the participants with higher levels of religiosity. This is in line with the conclusions reached in other studies with Chilean (Palermo et al, 2015;Pérez et al, 2020) and Latin American populations (Marván et al, 2018;McMurtrie et al, 2012;Sorhaindo et al, 2016) and in more distant cultures (Cockrill et al, 2013;Shellenberg et al, 2014). Likewise, considering the dimensions of religiosity included in this study, we can state that in addition to the acceptance of normative codes stemming from religious dogmas, interaction with other religious people -family members or peers -plays a role in this influence.…”
Section: Discussionsupporting
confidence: 92%
“…In a study with a community sample in Chile, religious people showed a perception of abortion as a serious crime, and they cited the dogma of the religion as their central argument for rejecting abortion (Pérez et al, 2020). Likewise, Palermo et al (2015) determined that the frequency of attendance at religious events was an important variable in the rejection of abortion among Chilean women. Furthermore, Baba et al (2020) and Biggs et al (2020) determined that medical and midwifery students at religious universities in Chile have moral and legal opinions that are more unfavourable towards abortion than students at secular universities.…”
mentioning
confidence: 99%
“…A higher level of education was one of the two factors which were independently associated to be against punishing any woman or women they know who had an abortion, is in agreement with other studies carried out in Latin America, showing that people with higher education are generally more in favor of less restrictive abortion laws [8,9]. What we did not found in the literature was any study that considered the personal history of unwanted pregnancy and previous abortion as a factor affecting people attitude toward abortion in general, or to punishing a woman who abort, in particular.…”
Section: Discussionsupporting
confidence: 90%
“…As more people come to adopt post‐material value systems, issues of personal choice and morality such as abortion and extending marriage rights to same‐sex couples enter the issue agenda. In keeping with this argument, we see that opinion on issues like abortion (Rossi and Triunfo, 2012; Palermo, Infante Erazo and Hurtado Pinochet, 2015; Küng et al, 2018) and same‐sex marriage (Dion and Díez, 2017; Navarro et al, 2019) divides along religious‐secular lines in several countries in Latin America. Because religious groups holding more traditional value systems tend to oppose policy liberalisation on these issues, divisions between religious and secular may persist or even intensify, polarising voters along religious and secular lines (Hildebrandt and Jäckle, 2019; Navarro et al, 2019).…”
Section: Religious‐secular Cleavages: Towards Dealignment?mentioning
confidence: 60%